2016
DOI: 10.1080/10253890.2016.1203417
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced decrease of uterine blood flow in sheep is mediated by alpha 1-adrenergic receptors

Abstract: Prenatal maternal stress can be transferred to the fetus via a catecholamine-dependent decrease of uterine blood flow (UBF). However, it is unclear which group of adrenergic receptors mediates this mechanism of maternal-fetal stress transfer. We hypothesized that in sheep, alpha 1-adrenergic receptors may play a key role in catecholamine mediated UBF decrease, as these receptors are mainly involved in peripheral vasoconstriction and are present in significant number in the uterine vasculature. After chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Another emerging application for fetal sheep models in the study of the programming of neurodevelopment is the evaluation of the impact of maternal stress during pregnancy, which is achieved by intermittent and unpredictable maternal isolation in the last trimester (102). Isolation is also used as a stimulus in progeny tests characterizing effects of the maternal environment (e.g., periconceptional undernutrition) on later postnatal HPA axis development in juvenile and adult sheep (182).…”
Section: Fact 9: Sheep Can Be Used In Neurodevelopmental Studies Owing To Similarities Between Stages Of Brain Development In Sheep and Hmentioning
confidence: 99%
“…Another emerging application for fetal sheep models in the study of the programming of neurodevelopment is the evaluation of the impact of maternal stress during pregnancy, which is achieved by intermittent and unpredictable maternal isolation in the last trimester (102). Isolation is also used as a stimulus in progeny tests characterizing effects of the maternal environment (e.g., periconceptional undernutrition) on later postnatal HPA axis development in juvenile and adult sheep (182).…”
Section: Fact 9: Sheep Can Be Used In Neurodevelopmental Studies Owing To Similarities Between Stages Of Brain Development In Sheep and Hmentioning
confidence: 99%
“…In a study, anxiety and chronic stress were found to increase serum cortisol and corticotrophin-releasing hormone in both mother and fetus resulting in dysregulations in the hypothalamic-pituitary-adrenal (HPA) axis in the fetus that in part causes structural abnormalities in the hippocampus, frontal cortex, amygdala, and nucleus accumbens (32). Further animal studies have also revealed a signi cant decrease in uterine blood ow due to stress (33)(34)(35). Human studies have also hypothesized a similar effect for stress and anxiety on uterine blood ow (12,17).…”
Section: Discussionmentioning
confidence: 99%
“…Those results were attributed to the deleterious effect of prolonged, sustained myometrial activity on fetal circulation, which significantly decreased gas exchange within the placenta and produced neonatal hypoxia in the fetus. Later studies confirmed that maternal stress produces hyperactivity of the HPA and the sympathetic–adrenal–medullary system, related to catecholamine release, elevated fetal blood pressure, and poor placenta-uterine perfusion [ 41 , 42 ].…”
Section: Controversy On the Participation Of Pain During Parturitionmentioning
confidence: 99%